Preparation and characterization of β-cyclodextrin grafted N-maleoyl chitosan nanoparticles for drug delivery - Xinyu Hou; Wenjuan Zhang; Muye He; Yiben Lu; Kaiyan Lou; Feng Gao (Elsevier, 2017)
β-cyclodextrin (CD) grafted N-maleoyl chitosan (CD-g-NMCS) with two different degrees of substitution (DS) of N-maleoyl (DS = 21.2% and 30.5%) were synthesized from maleic anhydride and chitosan bearing pendant cyclodextrin (CD-g-CS). CD-g-NMCS based nanoparticles were prepared via an ionic gelation method together with chitosan and CD-g-CS nanoparticles. The size and zeta potential of prepared CD-g-NMCS nanoparticles were 179.2~274.0 nm and 36.2~42.4 mV, respectively. In vitro stability test indicated that CD-g-NMCS nanoparticles were more stable in phosphate-buffered saline compared with chitosan nanoparticles. Moreover, a poorly water-soluble drug, ketoprofen (KTP), was selected as a model drug to study the obtained nanoparticle's potentials as drug delivery carriers. The drug loading efficiency of CD-g-NMCS20 nanoparticles were 14.8% for KTP. MTT assay showed that KTP loaded CD-g-NMCS nanoparticles were safe drug carriers. Notably, in vitro drug release studies showed that KTP was released in a sustained-release manner for the nanoparticles. The pharmacokinetic of drug loaded CD-g-NMCS20 nanoparticles were evaluated in rats after intravenous administration. The results of studies revealed that, compared with free KTP, KTP loaded CD-g-NMCS20 nanoparticles exhibited a significant increase in AUC0→24h and mean residence time by 6.6-fold and 2.9-fold, respectively. Therefore, CD-g-NMCS nanoparticles could be used as a novel promising nanoparticle-based drug delivery system for sustained release of poorly water-soluble drugs. The carboxylic acid groups of the CD-g-NMCS molecule provide convenient sites for further structural modifications including introduction of tissue- or disease- specific targeting groups.